The Influence of Tiktok Social Media on Generation Z's Preferences in Choosing Traditional Food in Garut Regency - Windi Wulandari; Yosef Abdul Ghani (International Journal of Travel, Hospitality and Events, 2025)
The impact of TikTok social media on Generation Z's preference for traditional food in Garut Regency is examined in this research. The study employed a quantitative technique with a survey methodology, and the data were gathered from 214 members of Generation Z using questionnaires. The reliability test confirms the validity of the instrument, while the validity test reveals that all indicators of TikTok Social Media (X) and Traditional Food Preference (Y) are valid. The data are suitable for regression analysis, according to classical assumption testing, which reveals that they are normally distributed and free of heteroscedasticity. Furthermore, Cronbach's Alpha is greater than 0.70. The regression results demonstrate that TikTok has a substantial and beneficial impact on Gen Z's preference for traditional cuisine, with a regression coefficient of 0.658 and a significance level of value of 0.000 p < 0.05. TikTok explains 44.5% of the variance in preferences, as shown by the coefficient of determination (R²), which is 0.445. According to the research, conventional culinary enterprises should use TikTok as a potent marketing platform to increase Generation Z's interest in traditional cuisine.